Estrous synchronization and fertility in allyl trenbolone-treated gilts - Stevenson, Jeffrey S.; Schmidt, W.E.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Onset of estrus in gilts fed allyl-trenbolone for either 14 or 18 days was controlled effectively. The stage of the cycle at the beginning of treatment had little effect on the synchronization response. More than 97% of the treated gilts showed estrus within 3 to 8 days after the last progestagen feeding. Treatment did not affect gestation length, farrowing rate, or litter size.
Keywords: Swine; Synchronization; Fertility; Allyl-trenbolone; Gilts